Instructional Leadership Role Through Kurt Lewin's Model to Enhance Culture of Change in Teacher Capabilities - Basthomi, Yazid Al; Sunandar, Asep; Timan, Agus (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The purpose of this research is to describe (1) the essence of instructional leadership in change management in educational institutions and (2) the change process in an elementary school during the unfreezing, movement, and refreezing stages to enhance the teaching capabilities of a teacher at SD Negeri Wonokerto 04. The research method used is qualitative, using a phenomenological approach with a case study design at SD Negeri Wonokerto 04, Malang Regency. The data were collected using three techniques: in-depth interviews, participant observation, and documentary study. The analysis technique used is single-case analysis. To ensure data validity, the researcher performed triangulation, member checking, prolonged observation, and reference material adequacy activities. The results of this study indicate that instructional leadership plays a role as a controller in the change process. The micro-educational institution's change process in enhancing the teaching capabilities of teachers follows Kurt Lewin's change model, which consists of three phases: a) the unfreezing process using symposiums and